An interactive e-learning module to promote bio-psycho-social management of low back pain in healthcare professionals: a pilot study. (4th March 2022) - Fourré, Antoine; Fierens, Auriane; Michielsen, Jef; Ris, Laurence; Dierick, Frédéric; Roussel, Nathalie
ABSTRACT: Introduction: Low back pain (LBP) is ranked as the first musculoskeletal disorder considering years lived with disability worldwide. Despite numerous guidelines promoting a bio-psycho-social (BPS) approach in the management of patients with LBP, many health care professionals (HCPs) still manage LBP patients mainly from a biomedical point of view. Objective: The purpose of this pilot study was to evaluate the feasibility of implementing an interactive e-learning module on the management of LBP in HCPs. Methods: n total 22 HCPs evaluated the feasibility of the e-learning module with a questionnaire and open questions. Participants filled in the Back Pain Attitude Questionnaire (Back-PAQ) before and after completing the module to evaluate their attitudes and beliefs about LBP. Results: The module was structured and easy to complete (91%) and met the expectations of the participants (86%). A majority agreed that the module improved their knowledge (69%). Some participants (77%) identified specific topics that might be discussed in more detail in the module. HCPs knowledge, beliefs and attitudes about LBP significantly improved following module completion (t = −7.63, P < .001) with a very large effect size ( ds = −1.63). Conclusion: I The module seems promising to change knowledge, attitudes and beliefs of the participants. There is an urgent need to develop and investigate the effect of educational interventions to favor best practice in LBP management and this type of e-learning support could promote the transition from a biomedical to a bio-psycho-social management of LBP in HCPs.